The Influence of Social Media Marketing Activities on Brand Loyalty: The Mediating Role of Brand Equity and Brand Trust among Indihome Customers in Kediri - Nizar Zakaria Nizar (Program Studi Akuntansi Universitas Islam Lamongan, 2026)
The increasing use of digital technology has transformed marketing practices in the telecommunications industry. Social media platforms have become strategic tools for companies to build customer relationships, strengthen brand perception, and improve customer loyalty. This study investigates the influence of social media marketing activities on brand loyalty through the mediating roles of brand trust and brand equity among IndiHome customers in Kediri, Indonesia. A quantitative research design was employed using a survey method. Data were collected from 300 IndiHome customers selected through probability sampling techniques. The data analysis process utilized Structural Equation Modeling (SEM) with AMOS software. Several statistical procedures were conducted, including validity testing, reliability testing, normality testing, goodness-of-fit analysis, and hypothesis testing. The findings demonstrate that social media marketing activities positively and significantly influence brand loyalty, brand trust, and brand equity. Furthermore, brand trust positively affects both brand equity and brand loyalty, while brand equity also positively influences brand loyalty. The mediation analysis reveals that brand trust significantly mediates the relationship between social media marketing activities and brand loyalty. However, the mediating effect of brand equity is relatively weaker. These findings indicate that effective social media communication can strengthen customer trust and enhance long-term customer loyalty in the telecommunications sector.